2015
DOI: 10.1007/s00165-014-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

A linear algebra approach to OLAP

Abstract: Inspired by the relational algebra of data processing, this paper addresses the foundations of data analytical processing from a linear algebra perspective. The paper investigates, in particular, how aggregation operations such as cross tabulations and data cubes essential to quantitative analysis of data can be expressed solely in terms of matrix multiplication, transposition and the Khatri-Rao variant of the Kronecker product. The approach offers a basis for deriving an algebraic theory of data consolidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Our work expands previous research that has been applied to several computer science domains [6,7,8,9], but our exposition steps further some leaps in the achievement of the original goal of combining category theory, linear algebra, and computer science in the derivation of MMM algorithms [4,5]. Our work relies on an improved expression of the GE using biproducts in section 3 and adapts the original formulations to combine general set functions and finite linear maps.…”
Section: Resultsmentioning
confidence: 71%
“…Our work expands previous research that has been applied to several computer science domains [6,7,8,9], but our exposition steps further some leaps in the achievement of the original goal of combining category theory, linear algebra, and computer science in the derivation of MMM algorithms [4,5]. Our work relies on an improved expression of the GE using biproducts in section 3 and adapts the original formulations to combine general set functions and finite linear maps.…”
Section: Resultsmentioning
confidence: 71%
“…The current paper resumes the work reported in [11] by showing how to express all data aggregation operators in LAoP, focussing on the data cube as central construction. Our main aim is to formalize previous work in the field -see e.g.…”
Section: Introductionmentioning
confidence: 88%
“…In [2] Abadir and Magnus stress on the need for a standardized notation for linear algebra in the field of econometrics and statistics. More recently, the authors have shown how data consolidation can be expressed in typed linear algebra [11], a categorial approach [10] to linear algebra which has shown useful elsewhere in the quantitative side of the software sciences, both at behaviour [14,18] and data [17] level.…”
Section: Introductionmentioning
confidence: 99%
“…Thinking of (28) as the pipeline of two components p = m 1 ⊕ m 2 and q = n 1 ⊕ n 2 with two-methods each, (29) gives us a composite (also two-method) machine whose methods are obtained by synchronizing the methods of p and q.…”
Section: Component Algebramentioning
confidence: 99%
“…This paper is part of a line of research aiming at promoting linear algebra as the "natural" evolution of (pointfree) relation algebra towards quantitative reasoning in the software sciences. Other applications of linear algebra in the software field [28,29,34,36,37] can be regarded as instances of the generic strategy put forward in this paper. Thus far, the main difficulty encountered in this technique is the fact that strong monads do not lift in general because the pairing operator lifts differently depending on the "branching" monad.…”
Section: Future Workmentioning
confidence: 99%